Controlling factors of continental shale oil mobility and resource potential in Dongpu Sag, Bohai Bay Basin - Hao LI; Jianlin LU; Baohua WANG; Kun LU; Yan ZHOU; Miao WANG; Linjie ZHAO; Zaichao SONG (Shiyou shiyan dizhi, 2020)
Good mobility is a key to the enrichment and high production of continental shale oil. Various data including thin section observation, scanning electron microscopy (SEM), X-ray energy spectrum (EDS), rock pyrolysis, high pressure mercury injection (HPMI) experiment were integrated to investigate the occurrence characteristics and major factors controlling shale oil mobility in the third member (Es3) of Shahejie Formation in the Dongpu Sag, Bohai Bay Basin. The distribution of movable oil resources was also predicted by using basin modelling. Shale oil mainly exists in intergranular pores, intercrystalline pores, dissolution pores and connected fractures in a free state, and is enriched around fractures. Maturity and fracture development are the main controlling factors of shale oil mobility. The influence of TOC content and porosity on shale oil mobility is relatively complicated. The shale in the middle and lower Es3 in the Dongpu Sag shows a great oil potential, mainly producing medium- and high-maturity oils. Movable oil is mainly distributed at a burial depth of 3 500-4 500 m, and is located in secondary depressions and inner slopes. The Qianliyuan Subsag, Wendong Inner Slope Zone, Puwei Subsag, Liutun Subsag, and Haitongji Subsag have higher movable oil abundances, which are the main exploration targets for continental shale oils.